Incidence Trends of Type 1 and Type 2 Diabetes among Youths, 2002–2012 - Bullock, Ann; Sheff, Karen; Mayer-Davis, Elizabeth J; Dabelea, Dana; Lawrence, Jean M (The New England journal of medicine, 2017)
To the Editor: In the SEARCH for Diabetes in Youth study, Mayer-Davis and colleagues (April 13 issue) 1 found a significant annual increase of 8.9% in the incidence of type 2 diabetes in the 2003–2012 period among Native American youths 10 to 19 years of age — the largest increase in any racial or ethnic group studied. However, the “Native American” youths on which these results are based are not representative of American Indian and Alaska Native youths nationwide. As the authors acknowledged in a previous article, “the number of [American Indian/Alaska Native] youth was small, was primarily from [Indian Health . . .